2020
DOI: 10.1111/hae.14154
|View full text |Cite
|
Sign up to set email alerts
|

3D gait analysis, haemophilia joint health score, leg muscle laterality and biomarkers of joint damage: A cross‐sectional comparative assessment of haemophilic arthropathy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 29 publications
4
21
2
Order By: Relevance
“…Studies comparing hemophilia patients and control patients showed both increased and decreased levels of cartilage, bone and synovial inflammation markers [7,8,10,11,[19][20][21]. These discrepancies were also noticed in our initial systematic review.…”
Section: Diagnosticsupporting
confidence: 48%
“…Studies comparing hemophilia patients and control patients showed both increased and decreased levels of cartilage, bone and synovial inflammation markers [7,8,10,11,[19][20][21]. These discrepancies were also noticed in our initial systematic review.…”
Section: Diagnosticsupporting
confidence: 48%
“…Associations between the HJHS and the physical activity parameters were assessed by Spearman's Rho. The targeted sample size of 24 PWH and 24 healthy controls was based on sample size calculation for the aforementioned primary study 19 . Differences in body composition between PWH and controls were additionally analysed in the subgroup of participants, who compliantly wore the accelerometer device for tracking physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity and body composition were recorded for this primary analysis in order to correct the primary effects for these potential confounding variables. 19 This prespecified secondary analysis aimed to evaluate physical activity patterns and body composition of adult PWH, by comparing these outcomes with those of healthy age-matched controls.…”
Section: Findings Reported In This Paper Represent a Secondary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis technique has been widely used as a functional diagnostic tool [ 8 ] to assist clinicians in their decision-making process to optimize the care of pathological individuals [ 9 ] such as hemophilic individuals [ 10 ]. In fact, previous studies have examined the gait patterns of individuals with hemophilia; however, they have reported only spatiotemporal parameters, joint angles, or pedobarography-related variables [ 11 , 12 , 13 ]. Few studies have employed 3D gait biomechanics to describe hemophilic gait patterns and most of those that did employ this technique had the subjects walk on a treadmill during the experiments [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%